(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
Our doctoral dissertation demonstrates that the export-oriented pastoral agro-industry in Brazil began growing in the 1920s, shaped by two continuous and interconnected trends. Exogenously, it stemmed from transformations in the global economy following the late nineteenth century, particularly the expansion of capital exports and consolidation of monopolies in core countries. On the other hand, it was also propelled by the diversification of investments originating from large coffee capital. As shown in the dissertation, the Brazilian agro-export model produced an economy marked by dependence, association, and subordination. We have examined the political mediation exercised by the Rural Society in shaping and advancing the national development project that ultimately materialised through the alliance between major domestic capital and international capital. In this vein, our research examines the First Republic—particularly the 1920s—by analysing the political mediation exercised by the period’s most influential agrarian employers’ association, the Brazilian Rural Society (SRB), and its role in shaping the national project for Brazil’s export-oriented livestock agribusiness. To do so, the scope of inquiry must be widened beyond Brazil’s borders to consider the international networks forged by the SRB across the Southern Cone, particularly its interactions with counterpart organisations such as the Argentine Rural Society (SRA) and the Rural Association of Uruguay (ARU). We have conceptualised the SRB as an agrarian interest group—an arena of power and consensus-building that articulated economic, political, and ideological interests. By positioning the SRB as a central actor in the development of the export-oriented livestock complex, we have advanced a novel interpretation of the political economy of the First Republic.